2012
DOI: 10.1002/mds.24999
|View full text |Cite
|
Sign up to set email alerts
|

Depression and quality of life in monogenic compared to idiopathic, early‐onset Parkinson's disease

Abstract: Quality of life (QoL) is decreased in PD and is linked with depression and anxiety. However, little is known about QoL in monogenic PD. Subjects with mutations in PD genes were recruited from ongoing family and genetic studies (manifesting carriers, n = 23; nonmanifesting carriers, n = 19). For comparison purposes, we included patients with idiopathic PD (IPD; n = 128; early onset, n = 38; late onset, n = 90), healthy controls (n = 127), and data on depressive symptoms of 144 patients with major depression (tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…These studies did not include nonmotor symptoms as independent variables. A recent systematic review concluded that depression, disease severity and disability negatively influence the patient-reported impact of PD and thus determined depression to be an important predictor of QOL (36). Similar results have been reported for anxiety (3)(4)(5); however, with insufficient supporting data (37).…”
Section: Discussionmentioning
confidence: 60%
“…These studies did not include nonmotor symptoms as independent variables. A recent systematic review concluded that depression, disease severity and disability negatively influence the patient-reported impact of PD and thus determined depression to be an important predictor of QOL (36). Similar results have been reported for anxiety (3)(4)(5); however, with insufficient supporting data (37).…”
Section: Discussionmentioning
confidence: 60%
“…Insomnia has a significant negative impact on QOL in PD [3,210-213,213,214]; at least 10% of patients with advanced PD rank sleep problems as their most bothersome symptom[185]. …”
Section: Insomniamentioning
confidence: 99%
“…1, 3 Insomnia significantly negatively impacts quality of life in PD. 49 Thus, effective and safe therapies for it are essential. Evidence supporting the use of hypnotics for treatment of chronic insomnia in PD is limited, and there are significant concerns for side effects, particularly increased fall risk.…”
Section: Introductionmentioning
confidence: 99%